KAJIAN TEOLOGIS SAMPA’ RAMPANAN KAPA’ DAN RELEVANSINYA BAGI KEHIDUPAN PERNIKAHAN WARGA JEMAAT GOLGOTA REA - Ronaldi Sirenden; Leoni Ombong Bone; Yuli Irsa Kalimbuang (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This research discusses the theological study of Toraja literature, namely sampa' rampanan kapa' conducted at the Toraja Church of the Golgota Rea Congregation. This research seeks to find out the meaning and value contained in sampa' rampanan kapa' and how it is relevant to the married life of the members of the Golgota Rea congregation. In this study, a qualitative research method was used with the type of field research. The results from the field show that the meaning contained in sampa' rampanan kapa' is advice on how to respect marriage and maintain the sanctity of marriage, while the values ??contained therein serve as role models in married life as are the hopes expressed in sampa' rampanan kapa '. Based on these meanings and values, this is very relevant in married life in the Golgotha ??Rea church, because it is still needed to maintain the sanctity of marriage.